2018
DOI: 10.18805/ijar.b-910
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of renal pathology in fish from Al-Hassa waterways, Saudi Arabia

Abstract: Pollution of aquatic environment is a great concern worldwide. The teleostean kidney is one of the first organ to be affected by contaminants in water. The aim of this study is to assess histological changes of Oreochromis niloticus kidney collected from spring canals in Al-Hassa, Saudi Arabia. We report histological alterations in the kidney tissue of fish collected from three sites, namely Al-Jawhariya (site #1), Um-Sabah (site #2) and Al-Khadoud spring (site #3). The histopathological studies revealed relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(34 reference statements)
1
0
0
Order By: Relevance
“…Most common alterations found in the kidney of fishes exposed to water contamination are tubule degeneration and changes in the corpuscle, such as dilation of capillaries in the glomerulus and reduction of Bowman´s space (Takashima and Hibiya, 1995). Our results are in accordance with Moneim et al (2019) reported disruption of kidney tissues in wild captured Nile tilapia, Oreochromis niloticus.…”
Section: Histopathological Changes In Kidney Tissuesupporting
confidence: 93%
“…Most common alterations found in the kidney of fishes exposed to water contamination are tubule degeneration and changes in the corpuscle, such as dilation of capillaries in the glomerulus and reduction of Bowman´s space (Takashima and Hibiya, 1995). Our results are in accordance with Moneim et al (2019) reported disruption of kidney tissues in wild captured Nile tilapia, Oreochromis niloticus.…”
Section: Histopathological Changes In Kidney Tissuesupporting
confidence: 93%